A Password and Least Significant Bit Substitution Based Steganography Technique for Image Hiding (International Journal of Innovative Research in Computer Science & Technology, 2023)
The proposed work introduces an image  steganography technique using text-based password that  acts as the symmetric key of encryption and decryption. It  contains two components, an encoder, and a decoder. An  encoder takes a secret image that needs to be hidden  inside another cover image. The Combined image is  encrypted with an eight characters’ password. The  starting position of the cover image from where the secret  image starts to hide depends on the password. Then the  (Least Significant Bit) LSB Substitution technique is used  to hide the entire secret image inside the cover image.  The decoder takes the encrypted image and the password  to retrieve the secret image back. The proposed work  produces an encrypted image by keeping 99%  information of the cover image and 100% information of  the secret image, thus it provides lossless retrieval of the  secret image. The proposed work includes dynamicity of  position in steganography that ensures more security of  image data over the network than the existing state of art  methods.
Keywords: Cryptography; Steganography; Least Significant Bit Substitution; Image Hiding